MODERN ENGLISH TEACHING METHODS - Amrillayeva Charosxon Rahmatillo qizi, (Ustozlar uchun, 2025)
This article explores modern English teaching methods, focusing on their definitions, classifications, implementation strategies, and significance in enhancing language acquisition. It examines innovative approaches such as communicative language teaching, task-based learning, and technology-enhanced instruction, alongside their applications in diverse educational contexts, including Uzbekistan. The study highlights the shift from traditional teacher-centered methods to learner-centered, interactive, and digital strategies that promote linguistic competence and cultural awareness. By analyzing the benefits, challenges, and future trends of these methods, the article offers insights for educators, policymakers, and researchers. Recommendations are provided to integrate modern methods into English language curricula, particularly in Uzbekistan, to support bilingualism and global communication.